Предмет:
МатематикаАвтор:
jack25-3х+3,6=1,4х - 5,2
-4,4х=-8,8
Х=2
(Х+3)*12=(2х-1)*5 мы все умножили на 60
12х+36=10х-5
41=-2х
Х=-20,5
-1,2х+2+0,6-1,5х=-6,04
-2,7х=-8,64
Х=3,2
0.6х-1.8-0.5х-0.5=1.5
0.1х-2.3=1.5
0.1х=3.8
Х=38
2х-4+5х=-6+3х
4х=-2
Х=-0.05
14х-8-4х+6=-39
10х=-37
Х=-3.7
Напиши в комментах если что то не понятно
Автор:
piggyДобавить свой ответ
Предмет:
БиологияАвтор:
buffieeccuОтветов:
Смотреть
Предмет:
МатематикаАвтор:
moralesjvkwОтветов:
Смотреть
Предмет:
ИсторияАвтор:
adisoncostaОтветов:
Смотреть
Предмет:
МатематикаАвтор:
brooklyn0tccОтветов:
Смотреть